2012
DOI: 10.1155/2012/368924
|View full text |Cite
|
Sign up to set email alerts
|

New and Simple Approach for Preventing Postoperative Peritoneal Adhesions: Do not Touch the Peritoneum without Viscous Liquid—A Multivariate Analysis

Abstract: Background. Postoperative peritoneal adhesions (PPAs) are an unsolved and serious problem in abdominal surgery. Method. Viscous liquids of soybean oil, octyl methoxycinnamate, flax oil, aloe vera gel, and glycerol were used in five experiments, using the same methodology for each. Liquids were applied in the peritoneal cavity before and after mechanical peritoneal trauma. Results were evaluated by multivariate analysis. Results. Compared with the control group, macroscopic and microscopic adhesion values befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Instead, most recent research has focused on short-term tissue engineering scaffolds and the utilization of PGA as a filler material coupled with other degradable polymer networks. PGA is often fabricated into a mesh network and has been used as a scaffold for bone, [27][28][29][30] cartilage, [31][32][33] tendon, 34,35 tooth, 36 vaginal, 37 intestinal, 38 lymphatic, 39 and spinal regeneration. 40 Although there has been research conducted into a wide range of applications, there exists significant issues with PGA.…”
Section: Polyglycolidementioning
confidence: 99%
See 1 more Smart Citation
“…Instead, most recent research has focused on short-term tissue engineering scaffolds and the utilization of PGA as a filler material coupled with other degradable polymer networks. PGA is often fabricated into a mesh network and has been used as a scaffold for bone, [27][28][29][30] cartilage, [31][32][33] tendon, 34,35 tooth, 36 vaginal, 37 intestinal, 38 lymphatic, 39 and spinal regeneration. 40 Although there has been research conducted into a wide range of applications, there exists significant issues with PGA.…”
Section: Polyglycolidementioning
confidence: 99%
“…Although glycolic acid is bioresorbable by cells via the citric acid cycle, 41 high level of glycolic acid have been linked to a strong, undesired inflammatory response. [42][43][44] In addition, PGA has mechanically failed as a biomaterial when used to facilitate colonic anastomosis formation 38 and prevent intrapericardial adhesions. 45…”
Section: Polyglycolidementioning
confidence: 99%
“…It has been shown that the addition of phospholipids that facilitate intestinal gliding after surgery can reduce the formation of PPA by 30% [ 19 21 ]. If viscous fluids are administered, particularly before mechanical manipulation, adhesion formation can be reduced, possibly as a result of a reduction in mechanical trauma [ 22 , 23 ]. Surfactant was also applied before applying the uterine horn adhesion procedure in the current experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Poly(lactic‐co‐glycolic acid) (PLGA) hollow fiber membranes prepared using the wet phase inversion method were used in nerve tract guidance conduits . Poly(glycolic acid) (PGA) is a material that has been successfully used in various applications including bone, cartilage, tooth, tendon, intestinal, vaginal, and spinal regeneration …”
Section: Synthetic Biomaterials To Modulate Stem Cellsmentioning
confidence: 99%